Past trajectory of a Northwest Europe socio-ecosystem at the land-sea interface: Case study of the northern watersheds of the Bay of Brest over the last 150 years - C. Valero; A. Penaud; M. Vidal; E. Goubert; P.A. Dessandier; S. Schmidt; E. Glémarec; P. Brigode; L. Bosseboeuf; Y.M. Paulet; J. Sutton; P. Ailliot; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Changes in French weather pattern seasonal frequencies projected by a CMIP5 ensemble - P. Brigode; M. Gérardin; P. Bernardara; J. Gailhard; P. Ribstein (International Journal of Climatology, 2018)
Over the last decades, general circulation model (GCM) simulations have been regularly evaluated in terms of their ability to reproduce the historical frequency of significantly recurrent weather patterns (WP) observed at the regional scale. Thus, a good simulation of the frequency of these particular WP by the GCM is generally conditioning the good representation of the regional statistics of surface variables such as temperature and precipitation. In this paper, the seasonal frequency of eight particular WP have been calculated using the daily geopotential height fields simulated by an ensemble of 26 Coupled Model Intercomparison Project Phase 5 (CMIP5) GCM. These WP are known as significantly influencing the French regional hydro‐climatology in terms of both frequency of low‐flows and high‐precipitation events. Four different bias correction methods have been applied on the simulated geopotential height fields before the calculation of the seasonal WP frequencies. The GCM ensemble showed overall good performances in terms of the simulation of WP seasonal frequencies. The application of a spatially and temporally non‐homogenous correction of simulated geopotential height fields improved significantly the simulation of WP frequencies for the four seasons. Finally, the evolution of the WP frequencies over the next century has been quantified. Three WP (WP2, WP4 and WP8) have pronounced seasonal changes, with WP2 and WP4 being less frequent in summer and autumn seasons, respectively, while WP8 being more frequent over spring, summer and autumn seasons. The strong simulated frequency evolution of WP2 and WP8 is an interesting result, which predicts the climate to be drier with time for France. Thus, WP2 (western oceanic circulation), grouping rainy days over the northern France region, is simulated as less frequent in future summers, while WP8 (anticyclonic situations), which groups non‐rainy days over France, is simulated as more frequent in future summers.

Dependence of model-based extreme flood estimation on the calibration period: case study of the Kamp River (Austria) - P. Brigode; E. Paquet; P. Bernardara; J. Gailhard; F. Garavaglia; P. Ribstein; F. Bourgin; C. Perrin; V. Andréassian (Hydrological Sciences Journal, 2015)

Parameter transferability under changing climate: case study with a land surface model in the Durance watershed, France - C. Magand; A. Ducharne; N. Le Moine; P. Brigode (Hydrological Sciences Journal, 2015)